Gambaran Latar Belakang Keluarga Korban Kekerasan Seksual di Kabupaten Siak Sri Indrapura - Zuhdi, Irvan; Arief, Yanwar (UIR Press, 2021)
Sexual violence against children is an act related to sexual activity committed by adults against children which can harm the child and provide a threat to the child so that the child is forced to comply with the wishes of the perpetrator of the crime. This research is a quantitative descriptive study that aims to explain or factually describe the topic of the study. This study aims to describe the family background of victims of sexual violence. The data collection method in this study used a questionnaire in the form of several questions containing the research objectives. The sample of the study was 52 parents whose children experienced sexual violence or harassment. The results of the study describe the family background of victims of sexual violence in this study, namely those from families with low economic levels, and negligence of parents towards their children, namely in the form of lack of supervision and lack of closeness (interaction) between parents and children.